Coping With Gender Norms. Constructions of Masculinity Between Autonomy and Dependence - Fidolini, Vulca (Italian Sociological Review, 2024)
This article aims to discuss gender identification processes as a dialectic of autonomy and dependence with respect to the production of hegemonic models of masculinity. The analysis which are proposed in this paper are based on results from a prolonged qualitative research on sexual conducts and construction of masculinities among young Moroccan and Muslim immigrant men living in Europe (France and Italy). By discussing specific case studies, I will analyse predatory masculinity – one of the hegemonic representations of “being a man” among the young people interviewed – as a gender performance where heterosexuality is conceived as an “essential” attribute of men. The text will first explore how this model of masculinity is configured as a normative reference by scientific literature on Islamic masculinities and among the young Moroccans I met. Then, I will show how this model allows the production of different social relations, especially between men, in homosocial spaces within immigrant milieu, and between Morocco and Europe. Finally, I will study the case of those young men who come to terms with this predatory model of masculinity in order to negotiate subordinate sexual orientations, such as homosexual. The paper will try to show how young men both develop new margins of manoeuvre to perform their masculinities and experience the coercive power of gender norms according to their social backgrounds and family origins. The main purpose of the text is an attempt to highlight both constricting and productive power of heterosexuality and its plural forms of expression.